Improving Creative Industry Production Performance during the Covid-19 Pandemic using Cost-Based Value Stream Mapping - Sri Indrawati; Amrullah Wahyu Adi Pratama; Umi Arief Nur'aini (Universitas Serang Raya, 2022)
Improvements in creative industry production performance during the COVID-19 pandemic is urgently needed to reduce production costs. Previous research has shown that improving industrial performance during the pandemic is still minimal. Implementing the lean manufacturing method using cost-based VSM is relevant to find out the industry's current value stream performance conditions and the potential savings in production costs. This research uses cost-based VSM to improve creative industry production during the COVID-19 pandemic. Based on the research results, three types of production waste are identified, i.e., motion, transportation, and inspection. Workstations have the most significant cost, i.e., tube making, making rings, and assembling. The lean action plan is then selected using several criteria: reducing lead time, increasing productivity, improving the quality of human resources, and increasing efficiency. With Implementing the lean action plan, process cycle efficiency is expected to increase by 5%, and production costs could be reduced by 0.45%.